2014
DOI: 10.1080/10522158.2014.924457
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Substance Use in Adolescence and Young Adulthood: The Role of Siblings

Abstract: Interpersonal relationships both within and outside the family have been a central part of alcohol and substance use research. Many studies have focused on the role of parents and peers; fewer studies have focused on siblings. This paper examined siblings' roles in ATOD use patterns and trajectories in the context of familial and non-familial factors across time. First, intraclass correlations (ICCs) were used to examine the degree to which older siblings' ATOD use was associated with younger siblings' ATOD us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 67 publications
1
24
0
3
Order By: Relevance
“…Multiple studies have demonstrated that siblings show significant levels of similarity for alcohol use in adolescence (Kokkevi, Richardson, Florescu, Kuzman, & Stergar, 2007; Kothari, Sorenson, Bank, & Snyder, 2014; Poelen, Engels, Van Der Vorst, Scholte, & Vermulst, 2007). Siblings close in age show the most synchronous levels of substance use (Kothari et al, 2014; Scholte, Poelen, Willemsen, Boomsma, & Engels, 2008; Trim, Leuthe, & Chassin, 2006) and co-sibling drinking has been shown to be more predictive of alcohol use in adolescence than parental drinking (Kothari et al, 2014; Scholte et al, 2008; Whiteman, Jensen, & Maggs, 2013), and heavy drinking by a sibling has been shown to convey a risk of similar magnitude to peer heavy drinking (Kokkevi, Richardson, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated that siblings show significant levels of similarity for alcohol use in adolescence (Kokkevi, Richardson, Florescu, Kuzman, & Stergar, 2007; Kothari, Sorenson, Bank, & Snyder, 2014; Poelen, Engels, Van Der Vorst, Scholte, & Vermulst, 2007). Siblings close in age show the most synchronous levels of substance use (Kothari et al, 2014; Scholte, Poelen, Willemsen, Boomsma, & Engels, 2008; Trim, Leuthe, & Chassin, 2006) and co-sibling drinking has been shown to be more predictive of alcohol use in adolescence than parental drinking (Kothari et al, 2014; Scholte et al, 2008; Whiteman, Jensen, & Maggs, 2013), and heavy drinking by a sibling has been shown to convey a risk of similar magnitude to peer heavy drinking (Kokkevi, Richardson, et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Siblings close in age show the most synchronous levels of substance use (Kothari et al, 2014; Scholte, Poelen, Willemsen, Boomsma, & Engels, 2008; Trim, Leuthe, & Chassin, 2006) and co-sibling drinking has been shown to be more predictive of alcohol use in adolescence than parental drinking (Kothari et al, 2014; Scholte et al, 2008; Whiteman, Jensen, & Maggs, 2013), and heavy drinking by a sibling has been shown to convey a risk of similar magnitude to peer heavy drinking (Kokkevi, Richardson, et al, 2007). Sibling collusion regarding deviant activities has also been shown to be related to AOD use (Stormshak, Comeau, & Shepard, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of family structure pertinent to alcohol use is the presence of siblings. While researchers have found parental drinking to encourage initiation of alcohol use among adolescents, sibling substance use is shown to reinforce and/or amplify the behavior 18,19 . Moreover, adolescents who observe their parents use alcohol to relax or siblings using smoking to facilitate social interaction, might also develop positive attitudes towards these substances and become more likely to engage in substance use themselves 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings reiterated that there was a strong relationship between older siblings' and younger siblings' substance use. However, siblings and peers appeared to be a powerful influence as the adolescent aged, but parents had a strong influence on their child's substance use early on in life (Kothari et al, 2014). Thus, family influence is a significant predictor of juvenile substance use.…”
Section: Generational Substance Usementioning
confidence: 95%
“…In addition to research displaying the strong relationship between generational offending and juvenile offending, substance use has also been revealed as intergenerational (Adler & Lotecka, 1973;Beardslee, Son, & Vaillant, 1986;Craig & Brown, 1975;Kothari, Sorenson, Bank, & Snyder, 2014;McDermott, 1984;Needle, McCubbin, Wilson, Reineck, Lazar, & Mederer, 1986;Tec, 1974). One study on the relationship between parental substance use and adolescent drug use examined a sample of 106 adolescent drug users and compared them to 96 non-drug using juveniles.…”
Section: Generational Substance Usementioning
confidence: 99%